Functional role of AKT signaling in bovine early embryonic development: potential link to embryotrophic actions of follistatin - Mohamed Ashry; Sandeep K. Rajput; Joseph K. Folger; Jason G. Knott; Nabil A. Hemeida; Omaima M. Kandil; Refaat S. Ragab; George W. Smith (BMC, 2018)
Abstract Background TGF-β signaling pathways regulate several crucial processes in female reproduction. AKT is a non-SMAD signaling pathway regulated by TGF-β ligands essential for oocyte maturation and early embryonic development in the mouse, but its regulatory role in bovine early embryonic development is not well established. Previously, we demonstrated a stimulatory role for follistatin (a binding protein for specific members of TGF-β superfamily) in early bovine embryonic development. The objectives of the present studies were to determine the functional role of AKT signaling in bovine early embryonic development and embryotrophic actions of follistatin. Methods We used AKT inhibitors III and IV as pharmacological inhibitors of AKT signaling pathway during the first 72 h of in vitro embryo culture. Effects of AKT inhibition on early embryonic development and AKT phosphorylation were investigated in the presence or absence of exogenous follistatin. Results Pharmacological inhibition of AKT signaling resulted in a significant reduction in early embryo cleavage, and development to the 8- to 16-cell and blastocyst stages (d7). Treatment with exogenous follistatin increased AKT phosphorylation and rescued the inhibitory effect of AKT inhibitors III and IV on AKT phosphorylation and early embryonic development. Conclusions Collectively, results suggest a potential requirement of AKT for bovine early embryonic development, and suggest a potential role for follistatin in regulation of AKT signaling in early bovine embryos.